A Narrative Draft on Positive Self-Category in Diverse Social- and Language World - DEVRAN, SERAP (ISTANBUL UNIV, FAC LETTERS, 2019)
This essay arose during my biographical- and interactional analysis of social and language experiences of young returnees, in other words, young women and men of Turkish origin, who grew up in Germany and Austria and re-migrated as teenagers or young adults to Turkey. Arda, the Informant, whom I want to introduce in the following, describes different social worlds in Germany and Turkey. For this, he describes two different which shaped his childhood; on one hand, it is the Turkish-World in Berlin/Kreuzberg, in which he was born into and remained until primary school and on the other hand, it is the German-World, in which his family later moved and where Arda was raised until the end of his primary school. After moving back to Turkey, Arda was introduced to a new modern Turkish environment, to which he had to become familiar. In his new world, Arda encounters the loss of his German daily language. For his description Arda uses complex methods of ethnic and social categorisation and more negative and/or positive self-positioning to different worlds. In order to describe his action, he used complex methods of ethnical and social categories and negative and/or positive self-positioning to diverse worlds. The aim of this work is primarily to give a general overview into the field of study of sociolinguistics and its social categories and secondarily the reconstruction of the categorisation-processes and linguistic methods Arda used.
Keywords: German-Turkish migration; biographical interviews; narrative identity; positioning; social categories